RxNav: A Progress Report - Zeng, Kelly (American Medical Informatics Association, 2005)
RxNav is a browser for RxNorm, the NLM repository of standard names for clinical drugs. RxNav displays links from clinical drugs, both branded and generic, to their active ingredients, drug components and related brand names. The current dataset comprises 5,546 ingredients, 7,718 brand names, 21,511 clinical drug components, 27,195 clinical drugs, 11,271 branded drugs, 12,598 clinical drug forms, 8,785 branded drug forms and 117 dose forms. RxNorm is one of a suite of designated standards for use in U.S. Federal Government systems for the electronic exchange of clinical health information. Since its introduction at Medinfo 2004, RxNav has undergone a series of improvements on its data format, functionality and architecture.